Arm modulation of triarylamines to fine-tune the properties of linear D–π–D HTMs for robust higher performance perovskite solar cells. (27th April 2021) - Zhang, Heng; Wu, Bingxue; Wu, Quanping; Wang, Zhihui; Xue, Song; Liang, Mao
Abstract : Most organic hole-transport materials (HTMs) toward efficient perovskite solar cells (PSCs) thus far still rely on methoxytriphenylamine, which limits the photovoltage and decrease the stability of PSCs. Abstract : Most organic hole-transport materials (HTMs) toward efficient perovskite solar cells (PSCs) thus far still rely on methoxytriphenylamine, which limits the photovoltage and decrease the stability of PSCs. However, alternative donors with better performance are scarce. Herein, we employ the synergistic strategy to modulate the properties of triarylamines (TAAs) by introducing different functional groups on their outer/inside arm. It is found that the arm modulation of asymmetrical TAAs can balance well the hole transport, HOMO level, film quality and stability of the studied HTMs M140 and M141. The photovoltaic performances of devices with doped and dopant-free M140 and M141 have been investigated. Encouragingly, the doped M141 device featuring the N -(9, 9-dimethyl-9 H -fluoren-2-yl)- N -(4-methoxyphenyl)spiro[fluorene-9, 9′-xanthen]-2-amine (MP-F-SFX) asymmetrical TAA achieves a significantly boosted power conversion efficiency (PCE) of 20.74%, accompanied by long-term stability in ambient air. This work not only provides a promising donor candidate (MP-F-SFX), but also reveals an effective way of using rationally designed asymmetrical triarylamines to fine-tune the properties of linear D–π–D HTMs.